1983
DOI: 10.1080/01688638308401169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pairing scanning training with block design training in the remediation of perceptual problems in left hemiplegics

Abstract: Twenty-seven left hemiplegics were divided into three groups of nine, matched for age, education, degree of left neglect, and time since onset of stroke. Subjects were pretested and, following the training, posttested on the WAIS Performance subtests, the WRAT Reading subtest, a letter cancellation task, an address-copying task, and a face-counting task. Subjects received 1 hour of occupational therapy (OT) each day for 20 successive days as follows: Group I received 1 hour of routine OT; Group II received 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 8 publications
1
35
1
1
Order By: Relevance
“…There is no evidence to suggest that recovery can, in fact, be influenced by such a mechanism. 12 This method of collecting data has two advantages. First, its simplicity makes it possible to have relatively complete information on a wide range of patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence to suggest that recovery can, in fact, be influenced by such a mechanism. 12 This method of collecting data has two advantages. First, its simplicity makes it possible to have relatively complete information on a wide range of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Group studies (not all were RCTs) have found significant differences between control groups of conventional rehabilitation and experimental groups receiving specialised perceptual treatment of various kinds, suggesting that their treatment techniques were of value in the remediation of perceptual problems (Diller et al, 1974;Weinberg et al, 1979;Weinberg et al, 1982;Young et al, 1983;Gordon et al, 1985). Diller et al (1974) in one of a series of studies involving both right and left hemiplegic stroke patients, investigated the effect of perceptual treatment following the transfer of training approach.…”
Section: Randomised Controlled Trial Studies Following the Transfer Omentioning
confidence: 99%
“…A study carried out by Young et al (1983) included 27 left hemiplegic patients who were aged 40 to 80 years. They were divided into three groups, matched for age, were from or how they were selected, suggesting there could have been some selection bias.…”
Section: Randomised Controlled Trial Studies Following the Transfer Omentioning
confidence: 99%
“…patients with brain damage (Ashman et al 2008, Burdea, 2003, Young et al 1983. Specifically, the patients set pegs into uniform slots on the pegboard.…”
Section: Introductionmentioning
confidence: 99%
“…And similar to SFA, block-design training requires patients to arrange blocks according to a prescribed model. Patients with brain damage who received block-design training have shown improved reading and word-writing skills through their enhanced visual information scanning ability (Young et al 1983). The SFA program showed improvements similar to those achieved through block-design training (Mochizuki-Kawai et al 2010).…”
Section: Introductionmentioning
confidence: 99%